Outcome of Mandibular Dentigerous Cysts 1 to 10 Years After Decompression Using a Custom-Made Appliance - MENTEŞ, ALİ RECAİ; UĞURLU, FAYSAL (W B SAUNDERS CO-ELSEVIER INC, 2021)
Purpose: The aim of this study was to examine the long-term results of mandibular dentigerous cysts treated with decompression using a custom-made appliance. Patients and Methods: This retrospective study included 34 patients with dentigerous cysts who were treated as outpatients at the Faculty of Dentistry, Marmara University. Medical history, complaints, intraoral and extraoral clinical findings, treatment time, and complications of these patients were collected. Results: The average age of the patients was 7.94 years. Three tooth buds (canine, first permanent premolar [P1], and second permanent premolar) in 2 cases, two tooth buds in 7 cases (P1 and second permanent premolar in 6 cases and P1 and canine in 1 case), and one tooth bud in 25 cases were related to the cyst. The mean decompression time was 5.97 months (range, 3 to 9 months). No major complications occurred during or after decompression. No evidence of infection, breakdown and/or dehiscence of the soft tissue, or inferior alveolar nerve paresthesia was observed. The complications and complaints were minor and straightforward to resolve. Conclusions: Decompression is a very effective and successful method for the treatment of mandibular dentigerous cysts. (C) 2020 American Association of Oral and Maxillofacial Surgeons